2018
DOI: 10.1097/cji.0000000000000202
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Immune-related Lipase Increase Induced by Antiprogrammed Death-1 or Death Ligand-1 Antibodies: A Brief Communication

Abstract: Antiprogrammed death-1 (anti-PD1) and antiprogrammed death ligand-1 (anti-PD-L1) antibodies are effective checkpoint inhibitors that stimulate the immune system against many types of cancers. The flip side of these immunotherapies is the generation of immune-related adverse events, which can theoretically affect all organs. Among these side effects, lipase increase is frequently observed; however the meaning of this biological abnormality remains poorly understood. We investigate in this case study all the lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 6 publications
2
25
1
Order By: Relevance
“…The clinical presentation of ICIPI was similar to the clinical picture of traditional acute pancreatitis, including epigastric pain, nausea and vomiting, fever, and diarrhea. Our findings are consistent with those of a case series of 21 patients with ICI-induced serum lipase elevation, in which 14% of patients developed symptoms of pancreatitis and 86% of patients were asymptomatic [21]. No statistically significant differences were found in that study regarding the presence of clinical symptoms in patients who received anti-CTLA-4–based therapy compared with those who received anti-PD-1/L1 therapy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The clinical presentation of ICIPI was similar to the clinical picture of traditional acute pancreatitis, including epigastric pain, nausea and vomiting, fever, and diarrhea. Our findings are consistent with those of a case series of 21 patients with ICI-induced serum lipase elevation, in which 14% of patients developed symptoms of pancreatitis and 86% of patients were asymptomatic [21]. No statistically significant differences were found in that study regarding the presence of clinical symptoms in patients who received anti-CTLA-4–based therapy compared with those who received anti-PD-1/L1 therapy.…”
Section: Discussionsupporting
confidence: 91%
“…This finding suggests that patients with asymptomatic ICIPI could have been undertreated owing to underestimation of the degree of ICIPI. This contradicts a previous recommendation to treat asymptomatic lipase elevation as an insignificant finding [21]. Our findings indicate that IV fluid administration should be considered, even in asymptomatic patients, for lipase elevation of grade 3 or higher, especially within 48 h of onset, to minimize long-term adverse outcomes.…”
Section: Discussioncontrasting
confidence: 91%
“…Previous studies have hypothesized that autoimmune T1DM is a combined endocrine–exocrine disease wherein loss of functional β-cell mass is most clinically apparent ( 122 ), and non-specific elevations in amylase and lipase occur in 16–25% of cases with DKA in ‘classic’ T1DM ( 123 ). In the context of ICI therapy, asymptomatic elevations in lipase and/or amylase have also been reported in the absence of new-onset DM ( 124 , 125 ). Several authors have also described radiographic changes in pancreatic volume during immunotherapy, notably pancreatic enlargement before DM onset followed by a decrease in volume ( 121 , 126 ).…”
Section: Immune Checkpoint Inhibitor-related Diabetes Mellitusmentioning
confidence: 99%
“…Several authors have also described radiographic changes in pancreatic volume during immunotherapy, notably pancreatic enlargement before DM onset followed by a decrease in volume ( 121 , 126 ). In the study by Michot et al , 3 of 21 patients (14%) developed clinical or radiologic immune-related pancreatitis that led to permanent treatment discontinuation in 15 of 21 (71%) patients, while the increase in lipase was not considered clinically significant, and treatment was continued ( 125 ). Ongoing pancreatic inflammation has been hypothesized to be a factor in the precipitation of DM; however, this is an additional question that should be addressed in prospective studies ( 109 , 127 ).…”
Section: Immune Checkpoint Inhibitor-related Diabetes Mellitusmentioning
confidence: 99%
“…Some authors recently demonstrated that high lipase level was not associated with pancreatic disease in most cases and should not be automatically associated with treatment cessation [72].…”
Section: Immune-related Adverse Events (Table 2)mentioning
confidence: 99%